Co-occurrence of mycotoxins in commercial formula milk and cereal-based baby food on the Qatar market. Issue 3 (3rd July 2018) - Ul Hassan, Zahoor; Al Thani, Roda; A. Atia, Fathy; Al Meer, Saeed; Migheli, Quirico; Jaoua, Samir
ABSTRACT: The present study was conducted to explore the occurrence of mycotoxins in commercial baby foods in Doha-Qatar. LCMS/MS- and HPLC-based analysis of baby food (n = 67) for 12 mycotoxins confirmed the presence of aflatoxin M1 (AFM1, 33%), ochratoxin A (OTA, 31%), deoxynivalenol (DON, 27%), aflatoxin B1 (AFB1, 22%), fumonisin B2 (FB2, 10%), zearalenone (ZEN, 4%) and T-2 toxin (2%). Noodles exhibited the maximum contamination percentage, with 33% of the samples being contaminated above the EU maximum limits, for at least one mycotoxin. Among the multi-grain flake samples, up to 28% and for the milk and milk-based-cereal samples, 14% contained at least one mycotoxin above the EU maximum limits. From all cereal-based food samples, 22%, 5%, 2% and 2% were concurrently contaminated with 2, 3, 4 and 5 mycotoxins, respectively. The occurrence of toxicological important mycotoxins in Qatari market warrants the implementation of strict regulatory limits to protect human health.